The Potential of REDD+ for Carbon Sequestration in Tropical Forests: Supply Curves for carbon storage for Kalimantan, Indonesia - Yonky Indrajaya; Edwin van der Werf; Hans-Peter Weikard; Frits Mohren; Ekko C. van Ierland (Fondazione Eni Enrico Mattei (FEEM), 2015)
We study the potential of tropical multi-age multi-species forests for sequestering carbon in response to financial incentives from REDD+. The use of reduced impact logging techniques (RIL) allows a forest owner to apply for carbon credits whereas the use of conventional logging techniques (CL) does not. This paper is the first to develop a Hartman model with selective cutting in this setting that takes additionality of carbon sequestration explicitly into account. We apply the model using data for Kalimantan, Indonesia. RIL leads to less damages on the residual stand than CL and has lower variable but higher fixed costs. We find that a system of carbon credits through REDD+ has a large potential for carbon storage. Interestingly, awarding carbon credits to carbon stored in end-use wood products does not increase the amount of carbon stored and reduces Land Expectation Value. We also observe that the level of the carbon price at which it becomes optimal not to harvest depends on the interpretation of the steady state model.
Keywords: Q2; Q23; 330; REDD+; Carbon Credits; Carbon Sequestration; Sustainable Forest Management; Reduced Impact Logging; Optimal Forest Management; Carbon Price